ANALISIS STRUKTUR CERPEN “SIKUT SUARA, GONG DOT KEN KANTIL DAN SWASTYASTU CINTA” KARYA PUTU AGUS SUTRARAMA - Ni Putu Winih Ayu Ariesta (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2025)
Literary works are the work of writers addressed to the public so that the contents of literary works can be implemented in life. Satua Bawak's literary works are included in the case of Bali Anyar or Modern literature in the form of prose which tells about the dynamics of modern human social life which has been affected by foreign influences. Satua Bawak in Indonesian is called Short Story, this short story has important things in each story that can be used as a reflection in life. This short story has intrinsic and extrinsic elements that the public or readers need to know. Swastyastu Cinta is a short story collection book which consists of ten short stories. The number of stories is only three that will be examined. The three titles of these short stories contain many important messages that can be used as guidelines in life.